An Exploration of How Social Media Data is Used in Companies, Evidence from the Telecom Industry - ZAMANI BAIDOKHTI, FARHOODEH (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2019)
ocial media (SM) has fundamentally changed how companies and consumers communicate and interact with each other. Comprehensive understanding of companies' use of SM requires an in-depth investigation of how companies use SM data, as well as the associated managerial challenges. Exiting studies of SM showcase a strong focus on the what research questions, such as SM's impacts and benefits which have been extensively discussed in the literature, while the how type of questions have received less attention. Review of the studies of companies' use of SM revealed that many studies show a range of potential benefits of using SM for companies. On the other hand, literature suggests a range of challenges companies are facing in dealing with SM data, which are mainly focused on the data related challenges. While the managerial challenges of using SM in companies need more academic attention, the wide range of potential benefits coupled with the discussed challenges highlight the need for insight into the details of the processes involved in using SM data in companies. Furthermore, the extant conceptual literature strongly suggests that SM data should be used in companies. However, the empirical evidence for a holistic and detailed view of how companies use SM data is lacking in the literature. Based on the above, the research questions for this study include: 'How is social media data used in companies?' and 'What are the managerial challenges in using SM data?' The empirical part of this thesis is comprised of a critical realist and qualitative case-based inquiry. Four cases were chosen from the telecom industry, as the most appropriate setting for the conduct of the research, which were believed to provide the required data richness and depth. Data from SM and marketing managers involved in the SM activities of the case companies were collected through interviews, and other sources of company documentation, reports, and observations. The collected data was then analysed using the detailed and systematic techniques in the Grounded Theory Data Analysis Method. The fruit of this analysis is the development of an outcome model which exposes three types of SM data use processes within companies, including proactive, reactive, and analytical SM data use process types, as well as three main subprocesses of content creation, individual SM data use, and aggregated SM data use. The findings of the study also revealed 12 stages of SM data use, which form the building blocks of the subprocesses. The combination of the revealed process types, subprocesses, and stages provide a holistic and detailed view of how SM data is used within companies. Moreover, the findings of this study reveal that SM information utilization includes instrumental, conceptual, and affective types of utilization, and it mainly happens in limited areas of business, in an immediate or short-term timeframe, and in relation to operational decisions. Regarding the managerial challenges of using SM, the findings reveal a number of managerial challenges which include content creation challenges (including creating constant, interesting, and real-time content, and finding the right balance between the promotional FGC and other types), customer related challenges (including SM negativity challenge, customers' high expectations challenge, and misinformation challenge), SM data actionability challenge, and resourcing challenge. The outcome model was then embedded in the context of the extant literature, delineating the main areas of contribution for this study. The thesis then puts forward the contributions, implications and recommendation for future research, subject to the discussed limitations.
APPROVED
Keywords: Social Media, Social Media Data Processing, Social Media Data Model, Using Social Media Data, Social Media Data Utilization, Managerial Challenges